Electrolyte membrane, method for producing the same, and battery
By introducing porous materials into the electrolyte to adsorb organic electrolytes, the problem of high-pressure molding of sulfur halide-based solid-state batteries was solved, enabling low-pressure molding and use of batteries, and improving the thermal stability and mechanical properties of the electrolyte.
Patent Information
- Application Number
- CN202511087022.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-05
- Publication Date
- 2025-12-30
- Estimated Expiration
- 2045-08-05
AI Technical Summary
Existing sulfur halide-based solid-state batteries require high-pressure molding and use during manufacturing and application, which leads to difficulties in equipment and structural design, especially when combined with silicon-based anodes.
By introducing porous materials to adsorb high-viscosity organic electrolytes and forming electrolyte complexes, the pressure of battery assembly and use is reduced, while maintaining high electrical performance and thermal stability.
This enables low-pressure molding and use of batteries, reducing the requirements for manufacturing equipment and structural components, while improving the thermal stability and mechanical properties of the electrolyte.
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to an electrolyte membrane prepared from an electrolyte complex having an organic electrolyte adsorbed by a porous material, a method for preparing the electrolyte membrane, and a battery having the electrolyte membrane. Background Technology
[0002] With the rapid development of new energy technologies, batteries have become one of the main directions for future energy development. Solid electrolytes, especially sulfide-based solid electrolytes, have high conductivity and are easy to cold-press, making solid-state batteries made from them a promising technology that is being vigorously developed. However, sulfide-based solid-state batteries typically require very high pressure for molding (generally 500-600 MPa), and the battery also needs to be subjected to high pressure continuously during operation, especially when paired with silicon-based anodes. This high-pressure manufacturing and high-pressure use poses significant challenges to the structural design of manufacturing equipment and downstream application scenarios. Summary of the Invention
[0003] To address the aforementioned issues, this application discloses an electrolyte in which porous materials are introduced and high-viscosity organic electrolytes are adsorbed through the porous materials. This enables the entire battery to be molded under low pressure and operate under low pressure, while simultaneously achieving high electrical performance and high thermal stability.
[0004] This application provides an electrolyte membrane, which may include at least: an inorganic electrolyte; an organic electrolyte complex, the organic electrolyte complex including: a porous material; and an organic electrolyte.
[0005] According to some embodiments of this application, the inorganic electrolyte may include one or a mixture of two of the following: halide solid electrolyte and sulfide solid electrolyte.
[0006] According to some embodiments of this application, the viscosity of the organic electrolyte at 25°C can be greater than 100 mPa·s.
[0007] According to some embodiments of this application, the average pore size of the porous material can be 0.5-10 nm.
[0008] According to some embodiments of this application, the organic electrolyte may include a eutectic electrolyte, which includes an organic compound and a lithium salt.
[0009] The organic compound is one or more of succinic anionyl nitrile, 1,3-dimethylimidazole, 2,2'-dithiodipyridine, urea, methylurea, and PES.
[0010] According to some embodiments of this application, the electrolyte membrane may also include an adhesive.
[0011] According to some embodiments of this application, the adhesive may be a fiber-reducible adhesive.
[0012] This application also provides a method for preparing the above-mentioned electrolyte membrane, the method comprising: S1. mixing porous materials, organic matter and lithium salt to obtain an organic electrolyte complex; S2. mixing the organic electrolyte complex obtained in step S1 with a fiberizable binder and an inorganic electrolyte and fiberizing to obtain an electrolyte complex; S3. forming the electrolyte complex obtained in step S2 into a film.
[0013] This application also provides a battery comprising an electrolyte membrane as described above or an electrolyte membrane prepared by the preparation method described above.
[0014] According to some embodiments of this application, the pressing pressure of the battery during the assembly and pressing process may not exceed 300 MPa.
[0015] This application significantly improves the thermal stability and mechanical properties of the electrolyte by introducing porous materials to adsorb the eutectic electrolyte into the electrolyte membrane, thereby reducing the high pressure required to maintain the solid-solid interface during battery manufacturing and use. Surprisingly, the electrolyte membrane prepared in this application also exhibits improved thermal stability.
[0016] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation
[0017] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the specific embodiments of this application are described in detail below. Many specific details are set forth in the following description to provide a thorough understanding of this application. However, this application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of this application. Therefore, this application is not limited to the specific embodiments disclosed below.
[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The terms “comprising” or “including” and similar terms used herein mean that an element or object preceding the word encompasses the elements or objects listed following the word and their equivalents, without excluding other elements or objects. The terms “and / or” or “and / or” as used herein include any and all combinations of one or more of the associated listed items.
[0019] The electrolyte disclosed in this application can be applied to lithium-ion batteries, enabling low-pressure molding during lithium-ion battery assembly and low-pressure operation. Some preferred embodiments of this application are described below. It should be noted that the following description is for illustrative purposes only and is not intended to limit the scope of protection of this application. The steps involved in this application can be performed precisely in sequence, or they can be processed in reverse order or simultaneously. Furthermore, other operations can be added to these processes, or one or more steps can be removed from these processes.
[0020] This application discloses an electrolyte membrane comprising at least an inorganic electrolyte and an organic electrolyte composite. The organic electrolyte composite may include a porous material and an organic electrolyte. The organic electrolyte may be adsorbed within the porous material and / or coated on the surface of the porous material. This electrolyte membrane can reduce the pressure during battery assembly and molding, and also reduce the operating pressure.
[0021] When manufacturing lithium-ion batteries using processes such as isostatic pressing, for batteries with a non-silicon anode, "low pressure" can refer to a process pressure of less than 300 MPa during isostatic pressing. In practical applications, a clamping pressure of less than 5 MPa can be considered a low pressure. For systems where the anode is primarily silicon-containing, higher pressure is required in practical applications to suppress the expansion of the silicon anode. Therefore, the range of low pressure differs slightly from that of non-silicon systems, being less than 10 MPa. Existing technologies clearly define silicon-containing and non-silicon systems. Systems with a large proportion of silicon-based active material and exhibiting expansion issues can be considered silicon systems. Systems with a small proportion of silicon-based active material or no silicon material, where there is essentially no performance degradation due to silicon expansion, can be considered non-silicon systems. It is understood that the fabrication and use of solid-state batteries at isostatic pressing pressures greater than 500 MPa and pressures greater than 5 MPa (non-silicon) or 10 MPa (silicon) are known in the art. The low-pressure molding and application scenarios of the system described in this application significantly reduce the requirements for battery production equipment and battery packs / modules that accommodate the batteries.
[0022] Therefore, the battery using the electrolyte described in this application can achieve low-pressure molding during assembly and low-pressure operation, significantly reducing the requirements for production equipment and structural components at the application end. Some preferred embodiments of this application are described below. It should be noted that the following description is for illustrative purposes only and is not intended to limit the scope of protection of this application. The steps involved in this application can be performed precisely in sequence, or various steps can be processed in reverse order or simultaneously. Furthermore, other operations can be added to these processes, or one or more steps can be removed from these processes.
[0023] In some embodiments, the inorganic electrolyte may include one or a combination of two of halide solid electrolyte materials and sulfide solid electrolytes. Exemplary examples include, but are not limited to, LaF3, LiCl, LiI, etc., or compounds with the chemical formula Li a MX b This refers to lithium halide solid electrolytes, where M represents a metallic or metalloid element, including one or more of B, Si, Ge, As, Sb, Te, Al, Zn, Mg, Ca, Ba, Mn, Cd, Co, Yb, Y, Cr, In, Ga, Sr, Hf, Ti, Ta, Sn, Nb, Er, Sc, etc., and X represents a halogen element such as F, Cl, Br, I, etc. Examples include Li₂CdCl₄, Li₂MgCl₄, Li₂CdI₄, Li₂ZnI₄, Li₂ZrCl₆, Li₃YCl₆, and derivatives produced by doping or coating Li₃InCl₆ or related materials.
[0024] Suitable, but not limited, sulfide solid electrolytes may include, but are not limited to, Li2S-P2S5 and Li2S-P2S5–MS. x (M=Si, Ge, Sn, 0≤x≤2), Li 9.6 P3S 12 Li7P3S 11 Li7P2S8I, Li 10 SnP2S 12 Li 10 SiP2S 12 Li9P3S9O3, LGPS(Li 10 GeP2S 12 Thio-LISICON (Li 3.25 Ge 0.25 P 0.75 S4), Li6PS5X (X=Cl, Br, I), Li3PS4-X (X=Cl, Br, I), Li4SnS4-X (X=Cl, Br), Li 3.25 Ge 0.25 P 0.75 S4, Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 Li 10.35 Ge 1.35P 1.65 S 12 Li 10.35 Si 1.35 P 1.65 S 12 Li 9.81 Sn 0.81 P 2.19 S 12 Li 10 (Si 0.5 Ge 0.5 P2S 12 Li 10 (Ge 0.5 Sn 0.5 P2S 12 Li 10 (Si 0.5 Sn 0.5 P2S 12 Li6 (PS5) 0.7 (GeS4) 0.3 Cl、Li 7.5 P 2.5 Sn 0.5 S 10.5 Cl 1.5 Li6PS5Cl 0.5 Br 0.5 Li6PS5I 0.2 Cl 0.8 Li5SnS2C l3 Li 10 P3S 12 Cl2, Li7P2S 8.5 Cl 0.5 Derivatives produced by doping or coating with materials such as or any combination thereof or related materials.
[0025] In some feasible implementations, the inorganic electrolyte can also be an oxide solid electrolyte material, a nitride solid electrolyte, a hydride solid electrolyte, a borate solid electrolyte, etc. For example, the oxide solid electrolyte may include, but is not limited to, NASICON-type solid electrolytes such as LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3, and Li... 1+x Al x Ge 2-x (PO4)3(LAGP, where 0 ≤ x ≤ 2), Li 1+x Al x Ti 2-x (PO4)3(LATP, where 0 ≤ x ≤ 2), Li 1+x Y x Zr 2-x(PO4)3(LYZP, where 0 ≤ x ≤ 2), Li 1.3 Al 0.3 Ti 1.7 (PO4)3, etc., perovskite-type solid electrolytes such as Li 3x La( 2 / 3-x )TiO3 (LLTO, where 0 < x < 0.25), LiSr 1.65 Zr 1.3 Ta 1.7 O9, Li 2x-y Sr 1-x Ta y Zr 1-y O3 (where x = 0.75y and 0.60 < y < 0.75), etc., LISICON-type solid electrolytes such as Li 14 ZnGe4O 16 、Li4SiO4、LiGeO4, etc., garnet-type solid electrolytes such as Li7La3Zr2O 12 、Li 6.5 La3Zr 1.75 Te 0.25 O 12 、Li 6.2 Ga 0.3 La 2.95 Rb 0.05 Zr2O 12 、Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 、Li 6.25 Al 0.25 La3Zr2O 12 、Li 6.75 La3Zr 1.75 Nb 0.25 O 12 、Li 6.75 La3Zr 1.75 Nb 0.25 O 12 etc., or derivatives produced by doping or coating improvement with any combination or related materials thereof.
[0026] Exemplary nitride solid electrolytes may include, but are not limited to, Li3N, Li7PN4, LiSi2N3, Li9N2Cl3, etc. Exemplary hydride solid electrolytes may include, but are not limited to, LiBH4, LiBH4-Li X(X = Cl, Br, or I), LiNH2, Li2NH, LiBH4-LiNH2, Li3AlH6, etc. Exemplary borate solid electrolytes may include, but are not limited to, Li2B4O7, Li2O-B2O3-P2O5, Li2B... 10 H 10 -Li2B 12 H 12 Examples include Li7N2I-0.5LiOH. Derivatives of these electrolytes obtained through substitution, doping, modification, and compositing can also serve as the inorganic solid electrolytes described in this application. For instance, bromine-substituted or partially substituted Li2ZrCl6, such as Li2ZrCl... 6-x Br x Rare earth metals such as lanthanum or yttrium-doped Li6PS5Br, and LLZO deposited on indium (In) surfaces, etc. It should be noted that the above examples are for illustrative purposes only and are not intended to limit the scope of this application.
[0027] The above-mentioned inorganic electrolytes can be presented in powder form, for example, by methods such as mechanical ball milling (e.g., weighing reactants according to stoichiometric ratio and then ball milling in an inert atmosphere (e.g., Ar / He), followed by annealing), high-temperature melt quenching (e.g., mixing reactants and heating to melt in an inert atmosphere, then rapidly cooling the solution and annealing), solution methods (e.g., dissolving the reaction precursor in an organic solvent and slowly evaporating the solvent in an inert atmosphere, then sintering to remove residual solvent and crystallizing), chemical vapor deposition (e.g., depositing a thin film on a heated substrate using vaporized feedstock and then annealing at low temperature), and solid-state reaction methods (e.g., uniformly mixing powdered reactants, pressing them into sheets, heating and holding in an inert atmosphere, followed by rapid cooling). This application does not impose specific limitations.
[0028] It is understood that the solid electrolyte material of this application is not required to be selected from any one of the above-mentioned materials, but may be selected from one or more of the above-mentioned solid electrolyte materials, such as a mixture of a sulfide solid electrolyte material and a halide solid electrolyte material, or a mixture of an oxide and two halide materials; without departing from the inventive concept of this application, the use of known conventional solid electrolytes should be considered within the scope of protection of this application.
[0029] As a preferred embodiment, the solid electrolyte material of this application is selected from a mixture of sulfide solid electrolytes and halide solid electrolytes, which has superior overall performance.
[0030] Porous materials can include covalent organic frameworks (COFs), metal-organic frameworks (MOFs), molecular sieves, zeolites, activated carbon, porous polymers, etc. For covalent organic frameworks (COFs), they can include two-dimensional layered framework structures such as TpPa-SO3H, TpPa-SO3Li, COF-1, COF-5, and LZU-1, or three-dimensional framework structures such as CTF, COF-300, CD-COF, and EB-COF. Of course, commercially available products such as A100, A520, CPO-27(Ni), and Basolite™ A101 can also be used as covalent organic frameworks.
[0031] Metal-organic framework materials such as MOF-5, MOF-74, MOF-505, MOF-525, ZIF-8, ZIF-67, HKUST-1, MIL-53, MIL-100, MIL-101, CPL-1, CPL-2, UiO-66, UiO-67, PCN-222, NU-1000, ZJU-7, and CPO-27 are applicable to this application.
[0032] Similarly, molecular sieves such as type A molecular sieves, X / Y molecular sieves, aluminum phosphate molecular sieves AlPO4-n, and titanium silicate molecular sieves TS-1, natural zeolites such as analcime, artificial zeolites such as ZSM-5, and activated carbons such as wood-based activated carbon, coal-based activated carbon, petroleum coke activated carbon, carbon nanotube activated carbon, and mesoporous activated carbon can be selected to constitute the porous material.
[0033] For porous polymers, they may include hypercrosslinked polymers (such as PIM-1), conjugated microporous polymers (such as CMP-1), self-microporous polymers (such as PAF-1), porous organic polymers (such as POP-1), dendritic macromolecules (such as PAMAM), porous aromatic frameworks (PAFs), hypercrosslinked polymers (such as PCH-1), self-assembled organic frameworks (such as SAOF-1), etc., or any combination thereof.
[0034] In some embodiments, the average pore size of the porous material can be between 0.5 nm and 10 nm. Optionally or preferably, the average pore size of the porous material can be between 1 nm and 9 nm. Optionally or preferably, the average pore size of the porous material can be between 2 nm and 8 nm. Optionally or preferably, the average pore size of the porous material can be between 3 nm and 7 nm. Optionally or preferably, the average pore size of the porous material can be between 4 nm and 6 nm. Optionally or preferably, the average pore size of the porous material can be between 4.5 nm and 5.5 nm. Alternatively, the average pore size of the porous material can be any value within the above range, such as 0.5 nm, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc. This application does not impose specific limitations.
[0035] Considering both the conductivity of the electrolyte and the low-pressure molding of the solid-state battery constructed with the electrolyte, a high proportion of porous material will reduce the conductivity of the electrolyte and decrease the battery's kinetic performance, while a low proportion will make low-pressure molding difficult. Therefore, the volume percentage of the porous material in the electrolyte can be 1-25%. Optionally or preferably, the volume percentage of the porous material in the electrolyte can be 2-20%. Optionally or preferably, the volume percentage of the porous material in the electrolyte can be 3-15%. Optionally or preferably, the volume percentage of the porous material in the electrolyte can be 4-10%. Optionally or preferably, the volume percentage of the porous material in the electrolyte can be 5-9%. Optionally or preferably, the volume percentage of the porous material in the electrolyte can be 6-8%. Alternatively, the volume percentage of the porous material in the electrolyte can be any value within the above ranges.
[0036] Organic electrolytes include eutectic electrolytes. These eutectic electrolytes may include organic compounds and lithium salts. Exemplarily, the organic compounds may include one or more of SN (succinate), (1,3-dimethylimidazolium), DpyDS (2,2'-dithiodipyridine), Urea (urea), and MU (methylurea) PES. The lithium salts may include, but are not limited to, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium trifluoromethanesulfonate (LiOTF), lithium hexafluorophosphate (LiPF6), lithium hexafluoroborate (LiBF6), lithium difluorooxalate borate (LiDFOB), lithium bis(oxalate borate) (LiBOB), lithium difluorophosphate (LiPO2F2), lithium hexafluoroarsenate, and tris(pentafluoroethyl) - Lithium trifluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium cyclodifluoromethane-1,1-bis(sulfonyl)imide, lithium cyclodifluoromethane-1,1-bis(sulfonyl)imide, lithium bis(perfluoroethanesulfonyl)imide, lithium bis(fluoromalonic acid)borate, lithium tetracyanoborate, lithium dicyanotriazole, lithium dicyano-trifluoromethyl-imidazolium, lithium dicyano-pentafluoroethyl-imidazolium, etc., or others. As examples, the eutectic electrolyte can be SN (butaniline)-LiTFSI, SN-LiFSI, DMIm (1,3-dimethylimidazolium)-LiTFSI, DpyDS (2,2'-dithiodipyridine)-LiTFSI, Urea (urea)-LiTFSI, MU (methylurea)-LiTFSI, etc. Among these, the SN and lithium salt (LiTFSI / LiFSI) are connected by a cyano group (-CN) and anion (TFSI). - / FSI - Strong interactions (such as dipole-dipole, hydrogen bonds) form a eutectic network, DMIm + As a cation and anion of LiTFSI (TFSI) - A eutectic structure is formed through electrostatic interactions, with the sulfur atoms of DpyDS reacting with Li. + Coordination, with TFSI - A coordination eutectic system is formed by the formation of multiple anions, and the amino group (-NH2) of urea / MU reacts with TFSI. - The fluorine atoms form strong hydrogen bonds, resulting in a stable eutectic network.
[0037] In some embodiments, the electrolyte membrane may further include an adhesive. Any known adhesive, including but not limited to polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aromatic polyamide resins, polyamides, polyimides, polyamide-imides, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, polyhexafluoropropylene, styrene-butadiene rubber, carboxymethyl cellulose, etc., or any combination thereof, may be used in this application. Copolymers may also be used as adhesives, exemplary of which may be copolymers of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, trifluorochloroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, hexadiene, etc. Alternatively, mixtures of two or more materials in the above examples may also be used as adhesives. In some implementations, the adhesive may include a fiber-reducible adhesive. For example, the adhesive may include, but is not limited to, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), styrene-butadiene rubber (SBR), cellulose, nanocellulose, nanofibers (CNF), polyaniline (PANI), polypyrrole (PPy), polyrotaxane, etc., or any combination thereof.
[0038] The electrolyte membrane disclosed in this application utilizes porous materials to provide confinement for the organic electrolyte complex, and surprisingly, this interaction can improve the thermal stability of the organic electrolyte. Simultaneously, after being combined with an inorganic electrolyte, it can improve the contact stability between the organic electrolyte complex and solid electrolytes (e.g., halide solid electrolytes or sulfide solid electrolytes). Furthermore, the porous material also helps to improve the mechanical strength of the electrolyte membrane.
[0039] This application discloses, in another aspect, a method for preparing the above-mentioned electrolyte membrane. As an exemplary but not limiting illustration, the preparation method may include the following steps:
[0040] S1. An organic electrolyte complex is obtained by mixing porous materials, organic matter, and lithium salt;
[0041] S2. The composite electrolyte obtained in step S1 is mixed with a fiberizable binder and an inorganic electrolyte and then fiberized to obtain an electrolyte composite.
[0042] S3. Form a film from the electrolyte complex obtained in step S2.
[0043] In some feasible implementations, porous materials, organic matter, and lithium salts can be weighed according to a preset mass ratio and then added to a mixing device for mixing. This device can be any suitable mixer, such as a high-speed mixing mixer or an air-flow mixing mixer. Relevant parameters, such as the high-speed dispersion rotation speed, can be between 1000 rpm and 10000 rpm. For example, high-speed dispersion rotation speeds could be 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm, 6000 ppm, 7000 ppm, 8000 ppm, 9000 ppm, or 10000 ppm. Optionally or preferably, the high-speed dispersion rotation speed is 4500 rpm to 7500 rpm. The high-speed dispersion time can be no more than 30 minutes, for example, 30 minutes, 25 minutes, 20 minutes, 15 minutes, 12 minutes, 10 minutes, 8 minutes, 6 minutes, 4 minutes, or 3 minutes. Optionally or preferably, the high-speed dispersion time is 5 minutes to 30 minutes. The airflow pulverization speed can be from 30 m / s to 100 m / s, for example, 30 m / s, 40 m / s, 50 m / s, 60 m / s, 70 m / s, 80 m / s, 90 m / s, or 100 m / s. The pulverization temperature can be from 25℃ to 60℃, for example, 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, or 60℃. After mixing, an organic electrolyte complex is obtained. In this process, the organic electrolyte is adsorbed or attached to the surface of the porous material.
[0044] For step S2, after weighing the organic composite electrolyte, the fiberizable binder, and the inorganic electrolyte according to the mass ratio, they can also be put into a mixer for high-speed shear mixing to allow the fiberizable binder to fiberize during the mixing process, thereby improving the mechanical properties of the mixture. A high-speed mixer can be used for step S2, and the mixing parameters can be adjusted according to different actual conditions. For example, the rotation speed can be 4500 rpm to 7500 rpm, and the dispersion time can be 5 min to 30 min. After mixing, the electrolyte composite is obtained.
[0045] In step S3, the electrolyte complex film formation can be achieved using methods such as molding, calendering, and rolling. For example, rolling can be used. One example is that the electrolyte complex can first be pre-formed, such as kneaded into a block or ground into a dough-like shape, and then placed in a rolling mill for hot rolling. This hot rolling can include multiple rolling processes. For example, multiple rolling processes can be performed by gradually decreasing the roll gap, ultimately resulting in an electrolyte film with the target thickness. This application does not impose specific limitations. When the organic electrolyte includes a eutectic electrolyte, the temperature of the hot rolling during the film formation process can be higher than the eutectic temperature of the eutectic electrolyte, thereby forming a stable phase.
[0046] This application also discloses a battery. The battery can be a single battery cell, and multiple battery cells can be folded, stacked, or arranged in combination to form a battery module. Exemplarily, the battery may include a positive electrode, a negative electrode, and an electrolyte membrane disposed between the positive and negative electrodes.
[0047] The positive electrode may contain materials capable of intercalating or deintercalating metal ions such as lithium ions, such as positive electrode active materials. Examples include lithium-containing transition metal oxides, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal fluorides, transition metal sulfides, or transition metal nitrides. Examples of lithium-containing transition metal oxides include Li(NiCoAl)O2 or LiCoO2.
[0048] The negative electrode can also be a material containing metal ions such as lithium ions that can be intercalated or deintercalated, such as a negative electrode active material. Examples include metallic materials (such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, Zn, etc., or alloys or compounds of the above metals, such as Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, TiO2-Li4Ti5O) 12 The anode material can be a lithium-based anode, such as Li-Al alloys, Ag-C alloys, etc., carbon materials (such as graphite including natural / artificial graphite, carbon fibers, soft carbon, hard carbon, crystalline carbon, amorphous carbon, etc.), and silicon compounds (such as silicon, silicon-carbon composites). In some embodiments, the anode may be a lithium-based anode. For example, the anode may be a lithium metal anode. Optionally, the anode may also be a silicon-based anode. For example, the anode may be made of a carbon-silicon composite and coated onto a copper foil serving as the anode current collector to form a anode sheet.
[0049] In some embodiments, the negative electrode can be an anode-free lithium metal solid-state battery, and the negative electrode can be made of Ag-C alloy and coated on copper foil, which serves as the negative electrode current collector, to form a negative electrode sheet (or negative electrode side structure).
[0050] The negative electrode may also include a binder, which may be the same as or similar to the binder used in the aforementioned positive electrode. For example, the binder used for the negative electrode may include polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl fluoride, polyethylene, polypropylene, etc. This application does not limit its application.
[0051] At least one of the positive or negative electrodes may also contain a conductive additive, such as carbon-based materials like graphite (natural or artificial graphite), carbon black (acetylene black or Ketjen black), carbon nanotubes, graphene, etc.; metal-based materials like metal powders (aluminum powder, nickel powder, etc.), metal oxides (titanium oxide, etc.), metal whiskers (alumina, oxidizing agents, etc.); conductive polymers like polyaniline, polypyrrole, polythiophene, etc.; and conductive fibers like carbon fibers, metal fibers, metal compound fibers, polymer fibers, etc. The conductive additive may also be one or a mixture of the above.
[0052] The electrolyte membrane can be the electrolyte membrane described above. See the foregoing for details.
[0053] The battery disclosed in this application operates at a pressing pressure not exceeding 300 MPa during the assembly and pressing process. For example, low-pressure pressing can be achieved when the various components constituting the battery are sequentially stacked, vacuum-sealed in an aluminum-plastic film, and then placed in an isostatic press for pressing. Compared to the high-pressure pressing (typically 500-600 MPa) required for existing sulfur halide solid-state batteries, low-pressure molding of the battery can be achieved. Furthermore, this battery can also be used at low pressure. For example, the operating pressure of a solid-state battery with a lithium-based anode can be 2-3 MPa (compared to 3-5 MPa for existing batteries), and the operating pressure of a solid-state battery with a silicon-based anode can be 3-10 MPa (compared to approximately 15 MPa for existing batteries).
[0054] The present application will be further described in detail below with reference to embodiments. It should be noted that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection claimed in this application.
[0055] Example 1
[0056] The eutectic organic electrolyte composition (SN:LiFSI) has a viscosity of 190 mPa·s;
[0057] SN: LiFSI: COF-F6: LPSCl: PTFE=11.35: 2.65: 6: 79.5: 0.5;
[0058] S1. Preparation of organic electrolyte complex: Mix COF and eutectic electrolyte in the corresponding mass ratio;
[0059] S2. Preparation of electrolyte complex: Li6PS5Cl, PTFE, and COF / eutectic complex were weighed according to the corresponding proportions and placed into a small high-speed mixer for mixing at 300 rpm. After mixing evenly, the mixture was taken out and repeatedly ground in a mortar until it became dough-like.
[0060] S3. Film formation: The dough-like mixture is rolled multiple times on a differential roller at a rolling temperature of 80°C and a speed ratio of 3:1 to obtain a dry sulfide electrolyte membrane with a target thickness of 100 μm.
[0061] Example 2
[0062] The eutectic organic electrolyte composition (propylene sulfonyl lactone-LiTFSI) has a viscosity of 410 mPa·s.
[0063] Propylene sulfonyl lactone: LiTFSI:COF-TpPaSO3Li:LiPSCl:PTFE = 7.16:6.84:6:79.5:0.5;
[0064] S1. Preparation of organic electrolyte complex: Mix COF and eutectic electrolyte in the corresponding mass ratio;
[0065] S2. Preparation of electrolyte complex: Weigh Li6PS5Cl, PTFE, and COF / eutectic complex according to the corresponding proportions and put them into a small high-speed mixer at a speed of 300 rpm. After mixing evenly, take it out and grind the mixture repeatedly in a mortar until it becomes doughy.
[0066] S3. Film formation: The dough-like mixture is rolled multiple times on a differential roller at a roller temperature of 80°C and a speed ratio of 3:1 to obtain a dry sulfide electrolyte membrane with a target thickness of 100μm.
[0067] Example 3
[0068] The eutectic organic electrolyte composition (SN-LiFSI) has a viscosity of 190 mPa·s;
[0069] SN: LiFSI: COF-F6: Li2ZrCl6: PTFE=11.35: 2.65: 6: 79.5: 0.5;
[0070] S1. Preparation of organic electrolyte complex: Mix COF and eutectic electrolyte in the corresponding mass ratio;
[0071] S2. Preparation of electrolyte complex: Weigh Li6PS5Cl, PTFE, and COF / eutectic complex according to the corresponding proportions and put them into a small high-speed mixer at a speed of 300 rpm. After mixing evenly, take it out and grind the mixture repeatedly in a mortar until it becomes doughy.
[0072] S3. Film formation: The dough-like mixture is rolled multiple times on a differential roller at a roller temperature of 80°C and a speed ratio of 3:1 to obtain a dry halide electrolyte membrane with a target thickness of 100μm.
[0073] Example 4
[0074] The viscosity of the eutectic organic electrolyte (tetrahydropyran: LiTFSI) is 596 mPa·s.
[0075] THP: LiTFSI: COF-TpPaSO3Li: LiPSCl: PTFE=4.73:9.27:6:79.5:0.5;
[0076] S1. Preparation of organic electrolyte complex: Mix COF and eutectic electrolyte in the corresponding mass ratio;
[0077] S2. Preparation of electrolyte complex: Li6PS5Cl, PTFE, and COF / eutectic complex were weighed according to the corresponding proportions and added to acetonitrile solution. The mixture was stirred at 300 rpm for 1 h and then dried under vacuum at room temperature for 5 h to obtain COF composite electrolyte.
[0078] S3. Film formation: The dough-like mixture is rolled multiple times on a differential roller at a roller temperature of 80°C and a speed ratio of 3:1 to obtain a dry sulfide electrolyte membrane with a target thickness of 100μm.
[0079] Comparative Example 1:
[0080] SN: LiFSI: LPSCl: PTFE=11.35: 2.65: 79.5: 0.5;
[0081] S1. Preparation of electrolyte complex: Weigh the above substances according to the corresponding proportions and put them into a small high-speed mixer at a mixing speed of 300 rpm. After mixing evenly, take it out and grind the mixture repeatedly in a mortar until it becomes doughy.
[0082] S2. Film formation: The dough-like mixture is rolled multiple times on a differential roller at a roller temperature of 80°C and a speed ratio of 3:1 to obtain a dry sulfide electrolyte membrane with a target thickness of 100μm.
[0083] Comparative Example 2:
[0084] SN: LiFSI: Li2ZrCl6: PTFE=11.35: 2.65: 79.5: 0.5;
[0085] S1. Preparation of electrolyte complex: Weigh the above substances according to the corresponding proportions and put them into a small high-speed mixer at a mixing speed of 300 rpm. After mixing evenly, take it out and grind the mixture repeatedly in a mortar until it becomes doughy.
[0086] S2. Film formation: The dough-like mixture is rolled multiple times on a differential roller at a roller temperature of 80°C and a speed ratio of 3:1 to obtain a dry halide electrolyte membrane with a target thickness of 100μm.
[0087] Comparative Example 3:
[0088] Propylene sulfonyl lactone: LiFSI: Li₂ZrCl₆: PTFE = 11.35: 2.65: 79.5: 0.5;
[0089] S1. Preparation of electrolyte complex: Weigh the above substances according to the corresponding proportions and put them into a small high-speed mixer at a mixing speed of 300 rpm. After mixing evenly, take it out and grind the mixture repeatedly in a mortar until it becomes doughy.
[0090] S2. Film formation: The dough-like mixture is rolled multiple times on a differential roller at a roller temperature of 80°C and a speed ratio of 3:1 to obtain a dry halide electrolyte membrane with a target thickness of 100μm.
[0091] Comparative Example 4
[0092] The viscosity of the eutectic organic electrolyte (butadienenitrile-LiDFOB-TXE) is 53 mPa·s.
[0093] Succinyl nitrile: LiDFOB: TXE: COF-TpPaSO3Li: LiPSCl: PTFE = 6.42:1.17:6.41:6:0.5;
[0094] S1. Preparation of organic electrolyte complex: Mix COF and eutectic electrolyte in the corresponding mass ratio;
[0095] S2. Preparation of electrolyte complex: Li6PS5Cl, PTFE, and COF / eutectic complex were weighed according to the corresponding proportions and added to acetonitrile solution. The mixture was stirred at 300 rpm for 1 h and then dried under vacuum at room temperature for 5 h to obtain COF composite electrolyte.
[0096] S3. Film formation: The dried mixture is rolled multiple times on a differential roller at a roller temperature of 80°C and a speed ratio of 3:1 to obtain a dry sulfide electrolyte membrane with a target thickness of 100μm.
[0097] Test case
[0098] 1. Methods for testing ionic conductivity
[0099] The prepared sulfur halide solid electrolyte membrane was cut into circular pieces with a diameter of 10 mm, clamped with metal pillars, and subjected to an external pressure of 375 MPa in a solid battery test mold for AC impedance testing in the frequency range of 8 MHz-1 Hz.
[0100] 2. Puncture strength test
[0101] The prepared sulfur halide solid electrolyte membrane was cut into circular pieces with a diameter of 19 mm, laid flat in the fixture of a puncture tester and clamped. Puncture was performed at a rate of 100 ± 10 mm / min, and the force measured during puncture was recorded. After the test, the sample was removed, and the thickness was measured at 4 points around the puncture hole. The average value was taken, and the puncture strength was calculated. Puncture strength = force at penetration / thickness of the halide solid electrolyte membrane.
[0102] 3. Thermogravimetric test
[0103] In an argon atmosphere glove box (oxygen level < 1 ppm), the prepared composite electrolyte membrane was weighed using a precision balance with an accuracy of 0.1 mg / 10,000, and its mass was recorded as m1 (m1 > 3 g). The membrane was placed in a covered ceramic boat and then placed in a muffle furnace within the glove box. The membrane was heated from room temperature (25℃ ± 3℃) to 120℃ at a heating rate of 5℃ / min and held at this temperature for 6 h. After natural cooling to room temperature (25℃ ± 3℃), the heat-treated composite electrolyte membrane was removed and weighed again, recorded as m2. The thermal weight loss rate R was calculated using the formula: R = (m1 - m2) / m1.
[0104] The relevant test results for the above embodiments are shown in Table 1 below:
[0105] Table 1 Test Results
[0106] Organic electrolyte (viscosity at 25°C, if applicable) Porous materials Inorganic electrolytes adhesive Ionic conductivity (mS / cm) Puncture strength (N / mm) Weight loss rate (%) after 6 hours of treatment in a 120°C glove box muffle furnace Example 1 SN-LiTFSI (eutectic electrolyte) viscosity 190 mPa s COF-F6 <![CDATA[Li6PS5Cl]]> PTFE 2.8 0.23 0.32 Example 2 Propylene sulfonate lactone-LiTFSI (eutectic electrolyte 410 mPas) <![CDATA[COF-TpPa-SO3Li]]> <![CDATA[Li6PS5Cl]]> PTFE 2.07 0.25 0.26 Example 3 SN-LiTFSI viscosity 190 mPa s COF-F6 <![CDATA[Li2ZrCl6]]> PTFE 1.31 0.65 0.34 Example 4 Eutectic: Tetrahydropyran (THP-LiTFSI) (viscosity 596 mPa·s) <![CDATA[COF-TpPa-SO3Li]]> <![CDATA[Li6PS5Cl]]> PTFE 1.01 0.23 0.31 Comparative Example 1 (Comparative Example 1) SN-LiTFSI / <![CDATA[Li6PS5Cl]]> PTFE 2.4 0.19 0.68 Comparative Example 2 (Comparative Example 2) Propylene sulfonate lactone / <![CDATA[Li6PS5Cl]]> PTFE 1.83 0.19 0.57 Comparative Example 3 (Comparative Example 3) SN-LiTFSI / <![CDATA[Li2ZrCl6]]> PTFE 0.1 0.47 0.74 Comparative Example 4 Succinate SN-LiDFOB-1,3,5-trioxane (TXE) (eutectic electrolyte 53 mPa s) <![CDATA[COF-TpPa-SO3Li]]> <![CDATA[Li6PS5Cl]]> PTFE 2.7 0.21 1.33
[0107] As shown in Table 1, the electrolyte membrane disclosed in this application, compared with electrolyte membranes in the prior art, has better ionic conductivity, superior puncture strength against puncture damage, and less thermal weight loss. Compared with electrolyte membranes in the prior art, the electrolyte membrane disclosed in this application has superior electrical and physical properties.
[0108] This application has described the basic concepts. Obviously, for those skilled in the art, the above detailed disclosure is merely illustrative and does not constitute a limitation of this application. Although not explicitly stated herein, those skilled in the art may make various modifications, improvements, and corrections to this application. Such modifications, improvements, and corrections are suggested in this application, and therefore such modifications, improvements, and corrections still fall within the spirit and scope of the exemplary embodiments of this application.
[0109] Furthermore, this application uses specific terms to describe its embodiments. For example, "an embodiment," "one embodiment," and / or "some embodiments" refer to a particular feature, structure, or characteristic related to at least one embodiment of this application. Therefore, it should be emphasized and noted that "an embodiment," "one embodiment," or "an alternative embodiment" mentioned twice or more in different locations in this application do not necessarily refer to the same embodiment. In addition, certain features, structures, or characteristics in one or more embodiments of this application can be appropriately combined.
[0110] Similarly, it should be noted that, in order to simplify the description of this application and thus aid in the understanding of one or more embodiments of the invention, the foregoing description of the embodiments of this application sometimes combines multiple features into one embodiment or its description. However, this disclosure method does not imply that the subject matter of this application requires more features than those mentioned in the claims. In fact, the embodiments have fewer features than all the features of the single embodiments disclosed above.
[0111] Finally, it should be understood that the embodiments described in this application are merely illustrative of the principles of the embodiments of this application. Other modifications may also fall within the scope of this application. Therefore, alternative configurations of the embodiments of this application are considered as examples and not limitations, and are regarded as consistent with the teachings of this application. Accordingly, the embodiments of this application are not limited to the embodiments explicitly described and illustrated in this application.
Claims
1. An electrolyte membrane, characterized by, At least comprising: an inorganic electrolyte, the inorganic electrolyte comprising a mixture of one or both of halide solid-state electrolyte, sulfide solid-state electrolyte; an organic electrolyte complex, the organic electrolyte complex comprising: a porous material; and an organic electrolyte, the organic electrolyte comprising a eutectic electrolyte; wherein, the volume ratio of the porous material in the electrolyte is 1-25%; the organic electrolyte will be adsorbed by the porous material; the organic electrolyte complex and the inorganic electrolyte are mixed by fiberizable binder after fiberization to participate in the composition of the electrolyte film.
2. The electrolyte film according to claim 1, characterized by The organic electrolyte has a viscosity greater than 100 mPa·s at 25℃.
3. The electrolyte film according to claim 1, characterized by The average pore size of the porous material is 0.5-10 nm.
4. The electrolyte film according to claim 1, characterized by The eutectic electrolyte comprises an organic matter and a lithium salt.
5. The electrolyte film according to claim 4, characterized by The organic matter is one or more of butanedinitrile, 1,3-dimethylimidazole, 2,2'-dithiodipyridine, urea, methylurea, and PES.
6. The method for producing an electrolyte membrane according to any one of claims 1 to 5, wherein The method comprises: S1. mixing a porous material and an organic matter, a lithium salt to obtain an organic electrolyte complex; S2. mixing the organic electrolyte complex obtained in step S1 with a fiberizable binder and an inorganic electrolyte to fiberize and obtain an electrolyte complex; S3. film forming the electrolyte complex obtained in step S2.
7. A battery comprising the electrolyte film according to any one of claims 1-5 or prepared by the preparation method of claim 6.
8. The battery of claim 7, wherein, The battery has a pressing pressure of no more than 300 MPa during the assembly pressing process.
Citation Information
Patent Citations
Preparation method of solid electrolyte composite diaphragm
CN118173971A
Composite solid electrolyte membrane, preparation method thereof and solid-state battery
CN118412531A